Muestra pictórica de la situación laboral en el sector bananero del cantón Santa Rosa, utilizando la técnica del óleo - Espinoza Rojas, Luis Lenín (2015)
Our work was conducted in rural areas of Santa Rosa Canton specifically focused on small and medium producers in the banana sector. This research was conducted with the aim to fulfill scientifically with prior to obtaining the title of Art investigative academic need, putting into practice the knowledge acquired in university classrooms, and contribute to the enrichment of literature on this important issue,